2019
DOI: 10.1002/humu.23768
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and clinical investigation of achromatopsia patients with mutations in the GNAT2 gene

Abstract: Achromatopsia (ACHM) is a hereditary cone photoreceptor disorder characterized by the inability to discriminate colors, nystagmus, photophobia, and low‐visual acuity. Six genes have been associated with this rare autosomal recessively inherited disease, including the GNAT2 gene encoding the catalytic α‐subunit of the G‐protein transducin which is expressed in the cone photoreceptor outer segment. Out of a cohort of 1,116 independent families diagnosed with a primary clinical diagnosis of ACHM, we identified 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 36 publications
(52 reference statements)
0
29
1
Order By: Relevance
“…S3). The observed color vision in our patient was better than previously reported residual color vision in GNAT2, 3,6,8 including the previously reported pedigree included in our study. 7 Despite the milder phenotype observed in patient P4, cone densities at all ROIs were the lowest in the cohort (Fig.…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…S3). The observed color vision in our patient was better than previously reported residual color vision in GNAT2, 3,6,8 including the previously reported pedigree included in our study. 7 Despite the milder phenotype observed in patient P4, cone densities at all ROIs were the lowest in the cohort (Fig.…”
Section: Discussioncontrasting
confidence: 46%
“…Felden et al in their genotyping study, reported a patient (CHRO768-II:1) with the same homozygous variant, without, however, any color vision or ERG data available. 8 Interestingly, this patient had undetectable standard light-adapted (LA30Hz; LA3) ERGs, when tested with Internationalstandard full-field ERGs, 54 and undetectable pattern ERG. 55 The recording to short wavelength flashes on an amber background (S-cone ERG; stimulus duration 5 ms) 56 was simplified and subnormal bilaterally ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations